Rendering Armed Struggle: OSPAAAL, Cuban Poster Art, and South-South Solidarity at the United Nations - Stites Mor, Jessica (Anuario de Historia de América Latina, 2019)
This article considers the role of the Organization of Solidarity with the Peoples of Africa, Asia, and Latin America (OSPAAAL) in championing a Latin American, tricontinentalist vision of Third World solidarity between these regions. It argues that Cuba used visual and media arts to frame and reframe historical evets, utilizing OSPAAAL as a conduit of pro-Cuba revolutionary ideas, as it circulated updates on national liberation struggles and calls to action for internationalist solidarity. OSPAAAL produced visual art in solidarity campaigns that allowed Cuba to promote a particular interpretation of the Cold War as ongoing colonialism to generate transnational support for national liberation struggles in the Middle East and Africa, as well as to promote the Cuban revolution itself. In particular, it examines the way that the visual approach used by the artists working with OSPAAAL intersected with other modes of transnational solidarity activism to promote revolutionary ideals and commonalities between distant participants and specifically in order to influence international cooperation at the United Nations and in advancing Castro’s profile within the Non-Aligned Movement.
Keywords: Internationalism, Solidarity, Cuba, Palestine, Latin America-Middle East Relations, Visual Culture.